Entangled Trajectories Based on Wigner Function with Negative Values (Journal of Atomic and Molecular Sciences, 2016)
Wigner function is a fundamental method to study the connection betweenquantum and classical system. Since negative value can be accepted by Wigner functioneven from a positive initial condition, they are various issues existing in correspondinginterpretation as well as the development of numerical methods. We presentthe entangled trajectories based on the Wigner distributions with negative values.